THE STUDENTS’ PROBLEMS USING AEGISUB TO MAKE SUBTITLE OF ENGLISH-INDONESIAN MOVIE - Andi Asmawati (Universitas islam Negeri Alauddin Makassar, 2020)
The aim of this research was to find out the students’ problems using Aegisub to make subtitle of English-Indonesian movie. Qualitative approach was used to describe the students’ problems faced during translating English into Indonesian languange (Bahasa). There were 16 students became the reprentative subjects. The data were collected through interview then it analyzed into 4 steps; they were coding, reducing, presenting, and concluding the data. The findings indicated that the students faced technical and linguistic problems. Technical problems were consisted of timing, typesetting, and iconifying. Linguistic problems related to the diction choices, equivalence, and translation strategies that the students used to deliver the meaning of the subtitle to the viewers. Thus, the students’ problems in making subtitle using Aegisub application were technical and linguistic problems.